Factors Determining Quality of Care in Family Planning Services in Africa: A Systematic Review of Mixed Evidence. - Gizachew Assefa Tessema; Judith Streak Gomersall; Mohammad Afzal Mahmood; Caroline O Laurence (PLoS ONE)
Background Improving use of family planning services is key to improving maternal health in Africa, and provision of quality of care in family planning services is critical to support higher levels of contraceptive uptake. The objective of this systematic review was to synthesize the available evidence on factors determining the quality of care in family planning services in Africa. Methods Quantitative and qualitative studies undertaken in Africa, published in English, in grey and commercial literature, between 1990 and 2015 were considered. Methodological quality of included studies was assessed using standardized tools. Findings from the quantitative studies were summarized using narrative and tables. Client satisfaction was used to assess the quality of care in family planning services in the quantitative component of the review. Meta-aggregation was used to synthesize the qualitative study findings. Results From 4334 records, 11 studies (eight quantitative, three qualitative) met the review eligibility criteria. The review found that quality of care was influenced by client, provider and facility factors, and structural and process aspects of the facilities. Client's waiting time, provider competency, provision/prescription of injectable methods, maintaining privacy and confidentiality were the most commonly identified process factors. The quality of stock inventory was the most commonly identified structural factor. The quality of care was also positively associated with privately-owned facilities. The qualitative synthesis revealed additional factors including access related factors such as 'pre-requisites to be fulfilled by the clients and cost of services, provider workload, and providers' behaviour. Conclusion There is limited evidence on factors determining quality of care in family planning services in Africa that shows quality of care is influenced by multiple factors. The evidence suggests that lowering access barriers and avoiding unnecessary pre-requisites for taking contraceptive methods are important to improve the quality of care in family planning services. Strategies to improve provider behavior and competency are important. Moreover, strategies that minimize client waiting time and ensure client confidentiality should be implemented to ensure quality of care in family planning services. However, no strong evidence based conclusions and recommendations may be drawn from the evidence. Future studies are needed to identify the most important factors associated with quality of care in family planning services in a wider range of African countries.